Analisa Efektivitas, Produktivitas dan Mutu Minyak Pada Mesin Empty Bunch Press Pabrik Kelapa Sawit - Mahyunis Mahyunis; Rafael Remit Winardi; Padamulia Raja; Giyanto Giyanto; Hafiz Darma Fazli (CV. IRA PUBLISHING, 2025)
The empty bunch press is a tool that extracts oil from empty palm fruit bunches to reduce oil losses. This study aimed to assess the machine's effectiveness and productivity, measure oil content in the residue, and evaluate the quality of the oil bunch press . A quantitative descriptive method was applied through 14 days of observation at a palm oil mill laboratory. Results showed that the oil content in empty bunches was 6.36%, that of residue was 1.12%, and that of oil bunch press was 5.23%. Input weight was 4,071 kg/hour, output 1,833 kg/hour, and extracted oil 95.87 kg/hour. The machine's effectiveness was 82.23%, and productivity was within a 5–6 tons/hour capacity. Oil bunch press quality tests showed 5.24% FFA, 0.41% moisture, and 0.12% impurities. Although losses and oil quality exceeded standard limits, the oil bunch press will be refined before blending with production oil.